The Knowledge Capabilities of the Vocabulary Component of a Medical Expert System - Bouhaddou, Omar (1990)
In this paper, we describe the ways in which medical knowledge is encoded into the knowledge base dictionary of an expert system (Iliad) designed as a teaching and consulting tool. Starting with a basic hierarchy, attributes have been added to facilitate the entry and display of patient data and inferencing about diagnosis and optimal work-up of the patient. For inferencing, a table of inter-term relationships has been added to the dictionary and techniques for deriving partial information using frequencies of occurrence of parent and child nodes in the hierarchy have been incorporated in the program. The disease independent knowledge included in the dictionary component is necessary to support the expert system's ability to make medically relevant and common sense inferences and generate realistic patient cases.